EVALUASI USABILITY PADA APLIKASI DIARYSUMSEL MENGGUNAKAN METODE USABILITY TESTING - Putra, Dodi Syahrial; Oktarina, Tri (ISTEK WIDURI, 2025)
DiarySumsel is a digital library application developed by PT. Woolu Aksara Maya (Aksaramaya) in collaboration with the National Library Agency of South Sumatra Province. This study aims to evaluate the application's usability using the Usability Testing method through task scenarios and the System Usability Scale (SUS) questionnaire. The results show a learnability score of 95% (good category), efficiency of 0.084 goals/second (highly efficient), and strong memorability based on a balanced average of clicks and steps. The error rate was only 4% (low), and the satisfaction score reached 69, which is above the average benchmark. Overall, DiarySumsel is considered to have good usability and effectively supports users in accessing digital library services.